Iron dynamics of boreal lakes inferred from iron speciation analysis of varved lake sediments - Björnerås, Caroline; Ojala, Antti E.K.; Hammarlund, Dan ; 0000-0001-7147-8173; Persson, Per; Kritzberg, Emma S. (Journal of Paleolimnology, 2025)
Iron (Fe) concentrations are increasing in lakes on a wide geographical scale, contributing to recent browning of lake waters. As available time series on lake-water Fe concentrations are relatively short, covering the past few decades only, varved lake sediments may provide extended and precisely dated records to study temporal Fe dynamics in lakes in response to environmental drivers, such as changes in catchment land use and atmospheric sulphur deposition. Here, we present and discuss temporal changes in Fe speciation and accumulation rates during the last three centuries as revealed by sub-annually resolved X-ray absorption spectroscopy analyses of varved sediments from three lakes in southern Finland. Iron speciation in sediments is dominated by Fe-bearing silicate fractions in two of the lakes, while the third lake has contributions of organically complexed Fe and Fe-(oxy)hydroxides. Long-term changes in sediment Fe accumulation correspond with documented shifts in land use from agriculture to spruce forestry in the lake catchments, and in one of the lakes with water-level lowering. An overall poor correspondence between monitored aqueous Fe concentrations and sediment-inferred Fe accumulation rates is likely linked to the dominance in the sediments of particulate Fe phases that are not prevalent in suspended form in the water column. This suggests that sediment records are unsuitable for reconstructions of past lake-water Fe concentrations in these lakes. However, the study provides valuable insight into how major land-use changes in the past have affected both the supply and speciation of Fe accumulated in lake sediments.
Publisher Copyright: © The Author(s) 2025.
Keywords: Iron biogeochemistry; Iron speciation; Micro X-ray fluorescence; Palaeolimnological reconstruction; X-ray absorption spectroscopy